PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP KETERAMPILAN BERBICARA BAHASA INDONESIA SISWA KELAS IV MI MUHAMMADIAYAH 02 PEKANBARU - Susanti, Desy (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2025)
This study aims to examine the effect of the Think Pair Share (TPS) learning model on the speaking skills of fourth-grade students at MI Muhammadiyah 02 Pekanbaru. The research employed a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 50 students, with 25 students in class IV A as the experimental group and 25 students in class IV B as the control group. The instrument used was a speaking skills test assessed with a rubric including fluency, pronunciation accuracy, sentence structure, and confidence. The results showed a significant improvement in speaking skills. The average speaking score of the experimental class increased from 67.4 to 82.6 (an improvement of 15.2 points), while the control class increased from 66.8 to 73.2 (an improvement of 6.4 points). The N-Gain score in the experimental class was 0.428 (moderate category). The prerequisite tests indicated that the data were normally distributed and homogeneous, allowing the t-test to be applied. The independent t-test result showed sig. (2-tailed) = 0.001 < 0.05, indicating a significant effect of the TPS model on students’ speaking skills. Therefore, TPS can be considered an effective alternative strategy in Indonesian language learning to enhance students’ speaking skills at Madrasah Ibtidaiyah